MOR202, a novel anti-CD38 monoclonal antibody, in patients with relapsed or refractory multiple myeloma: a first-in-human, multicentre, phase 1–2a trial. Issue 5 (May 2020) - Raab, Marc S; Engelhardt, Monika; Blank, Antje; Goldschmidt, Hartmut; Agis, Hermine; Blau, Igor W; Einsele, Hermann; Ferstl, Barbara; Schub, Natalie; Röllig, Christoph; Weisel, Katja; Winderlich, Mark; et al.
Summary: Background: Treatment of multiple myeloma is not curative, but targeting CD38 improves patient survival. To further explore this therapeutic approach, we investigated the safety and activity of MOR202, a novel monoclonal antibody targeting CD38, in patients with multiple myeloma. Methods: This is a multicentre, open-label, phase 1–2a trial done at ten hospitals in Germany and Austria. Enrolled patients were aged 18 years or older with relapsed or refractory multiple myeloma and Karnofsky performance status of 60% or higher. Patients were assigned to the different treatment regimens with MOR202 ranging between 0·01 mg/kg and 16 mg/kg in a 3 + 3 design. Dose-escalation and expansion was done either with MOR202 intravenous infusions alone (MOR202 q2w [twice a week] and q1w [weekly] groups) or in combination with dexamethasone (MOR202 with dexamethasone group), with dexamethasone plus pomalidomide (MOR202 with dexamethasone plus pomalidomide group) or plus lenalidomide (MOR202 with dexamethasone plus lenalidomide group). Primary endpoints were safety, MOR202 maximum tolerated dose (or recommended dose) and regimen, and immunogenicity. The primary analysis was assessed in the safety population, which included patients who received at least one dose of any study drug. This trial is registered with ClinicalTrials.gov, NCT01421186 . Findings: Between Aug 24, 2011, and Aug 1, 2017, 91 patients were treated, 35 with MOR202 monotherapy, and 56 with MOR202 combination regimens (18 in the MOR202 with dexamethasone group, 21 in the MOR202 with dexamethasone plus pomalidomide group, and 17 in the MOR202 with dexamethasone plus lenalidomide group). MOR202 intravenous infusions were safely administered within 30 min. Infusion-related reactions occurred in 14 (40%) of 35 patients receiving MOR202 monotherapy without steroids, and in four (7%) of 56 patients receiving MOR202 combination treatment. MOR202 maximum tolerated dose was not reached and the recommended regimens were MOR202 administered as an intravenous infusion for 30 min at doses up to 16 mg/kg with dexamethasone (40 mg), or in combination with dexamethasone plus lenalidomide (25 mg) or pomalidomide (4 mg). 35 (38%) of 91 patients developed lymphopenia, 30 (33%) developed neutropenia, and 27 (30%) developed leukopenia; these were the most common grade 3 or higher treatment-emergent adverse events. Serious adverse events were reported in 51 (56%) of 91 patients. None of the deaths were associated with MOR202. One pomalidomide-associated death occurred in the MOR202 with dexamethasone plus pomalidomide group. No anti-MOR202 antibodies were detected in patients. Interpretation: MOR202 is safe and its clinical activity in patients with relapsed or refractory multiple myeloma is promising. Further clinical investigations of combinations with an immunomodulatory drug and dexamethasone are recommended. Funding: MorphoSys AG.